POSISI ARSIP DAN SEJARAH KELUARGA DALAM HISTORIOGRAFI INDONESIA: Array - Pratika Rizki Dewi; Arfan Habibi; Ratna Bella Sari (Arsip Nasional Republik Indonesia, 2020)
The family is the smallest social unit in society. Files or records are also created witihin the family. Family files are documents relating to the family such as personal identity, family identity, diplomas, photos, diaries up to personal letters. Family files are historical sources, part of them are primary ones, and crucial for historians. By implementing historical methods, the article suggests that they are available within various forms, they are historical sources and because of that they are crucial within Indonesian historiography.